Long-term effects of sheep-grazing and its removal on vegetation dynamics of British upland grasslands and moorlands; local management cannot overcome large-scale trends. (June 2022) - Alday, Josu G.; O'Reilly, John; Rose, Rob J.; Marrs, Rob H.
Graphical abstract: Highlights: We measured change in four British upland communities between 1953 and 2016. Replicated grazed-ungrazed plots were compared at 12 sites within 4 communities. We modelled long-term change in richness and abundance of 4 plant taxonomic groups. There is evidence of post-2000 recovery in vascular plants and mosses. There is limited liverwort and no lichen recovery; they are a restoration priority. Abstract: The upland and mountainous regions of northern Europe provide a wide variety of ecosystem services. However, these ecosystem services are highly vulnerable to environmental and land-use change. To ensure their future conservation, it is therefore, essential to understand whether upland plant communities will respond positively or negatively to a range of environmental factors such as grazing pressure and landscape-scale factors such as changes in atmospheric SO2 and NOx deposition. To understand this, here, we describe the long-term trends in four UK upland communities (high-level grassland, intermediate grassland, blanket bog, high-level bog) using four replicated long-term experiments examining the effects of sheep grazing compared to no-sheep grazing in Moor House (from 1954 to 2016). Our results showed that species richness and abundance recovered in grazed plots after 2000, with improvements in species richness and abundance of vascular plants, mosses, and liverworts. Unfortunately, no improvement was found for lichens. Species richness, vascular plants, and mosses recovered the fastest, and much faster than liverworts. There was no evidence of slower recovery of species richness and abundance in plots where sheep grazing was removed. These results are consistent with longitudinal studies suggesting recovery after 2000 as a result of reduced atmospheric deposition. Although trends in diversity and abundance in the grazed and ungrazed plots were not identical, they were not markedly different either. The similar richness and abundance trends in the grazed and ungrazed plots found in each plant community suggest that within-community dynamics may overcome initial differences between the grazing treatments over time. In contrast, differences in richness and abundance among plant communities over time suggest that some landscape-scale trends, such as those caused by a reduction in nutrient inputs, initiate community-dependent recovery.